Computational influences of convection micropolar fluid influx and permeability on characteristics of heating rate and skin friction over vertical plate - Omar Quran; Abdullah N. Olimat; Hussein Maaitah; Hamzeh M. Duwairi (International Journal of Thermofluids)
This manuscript merits at examining of an embedded orthogonal plate inside porous domain exposed to uniform heat influx to elaborate on how micro polar fluid factors and permeability characteristic affect the local skin friction, heating rate, and angular velocity inside boundary layer. The plate is subjected to forced convective micro polar fluid influx under steady, incompressible, and viscous circumstances. To facilitate dependable numerical solution, similarity approach is implemented to mutate set of coupled governing equations relevant to the adopted study into a constrained dimensionless differential equations. Computational analysis has been executed hiring Runge-Kutta scheme by Matlab function bvp4c to settle the governing equations. Study's results are highlighted graphically the impact of micro polar fluid factors on the local skin friction, heating rate, and angular velocity curves. High degree of acceptability of present findings compare with prior research results. It is found that the rising of Darcy parameter drives to decrease linearly both heating rate and local skin friction. Among the examined factors, the benchmark parameter of decreasing skin friction is the porosity. Additionally, it is found that an increasing of Prandtl number and micro rotation element lead to enhance Nusselt number. Once curves of micro rotation are interfered at certain distance from the plate due to increase in porosity, Darcy, Forchheimer's, and microelement rotation, the micro rotation curves are inverted.